Pathogenicity Analysis of Weaned Piglets Challenged With Novel Emerging Senecavirus A in Fujian, China - Liu, Cun; Liu, Yanhan; Li, Xiubo; Liang, Lin; Cui, Shangjin (Frontiers in Veterinary Science, 2021)
In order to evaluate the pathogenicity of Seneca virus A (SVA) to weaned piglets preliminarily, 28-day-old weaned piglets were challenged with SVA by intramuscular injection. The clinical manifestations, antibody levels and tissue viral load of infected piglets were detected. The results indicated that the piglets challenged with SVA CH/FuJ/2017 showed drowsiness, lameness, oral blisters, diarrhea, and other clinical signs. The lesions on foot were observed. Red spots or plaques were initially observed on the hoof, and then developed into blisters which cracked and gradually formed scab. The symptoms signs were relieved after 8 dpi. The sentinel piglet, feeding together with the challenged piglets, showed similar clinical signs with the challenged piglets after 3 dpi. The monitor of antibody levels showed that anti-SVA antibody could be detected at 5 dpi by cELISA method and neutralizing antibody could be detected after 7 dpi. Analysis of viral tissue distribution and viral load indicated that SVA could replicate in liver, spleen, lung, kidney, and lymph node. In all, Seneca virus disease was successfully replicated by SVA CH/FuJ/2017 isolate, which verified the clinical manifestations of SVA infection in weaned piglets, and provided a foundation for further SVA pathogenesis and vaccine development.